Efektivitas Pupuk Cair Berbasis Limbah Pertanian Terhadap Pertumbuhan Tanaman Sayuran - Rian Alpian (CV. SINAR HOWUHOWU, 2026)
The utilization of agricultural waste as organic fertilizer is an important approach to support sustainable agriculture and reduce dependence on synthetic chemical fertilizers. This study aimed to analyze the effectiveness of liquid fertilizer derived from agricultural waste on the growth of vegetable crops. An experimental method was applied using a completely randomized design (CRD) with several liquid fertilizer dosage treatments. Growth parameters observed included plant height, number of leaves, and fresh weight of plants. The collected data were analyzed using analysis of variance (ANOVA) to determine the effects of the treatments. The results showed that liquid fertilizer based on agricultural waste had a significant effect on all observed growth parameters of vegetable crops. Increasing fertilizer dosage tended to enhance plant growth. The study concludes that agricultural waste–based liquid fertilizer is effective in improving vegetable crop growth and has strong potential as an environmentally friendly alternative fertilizer to support sustainable agricultural systems.